Environmental Technological Innovation and Its Contribution to Sustainable Development - Muhammad Fakhrul, Yusuf; Hasbullah, Ashari; Mohd Rizal, Razalli (Faculty of Engineering, Universitas Indonesia, 2018)
Globally, global warming, resource depletion, and increased solid waste volumes have become major concerns for international governments. This paper aims to address Malaysia’s competitiveness in the context of global environmental change by analyzing firms that have incorporated environmental technological innovation (ET innovation) in their operations. This paper illustrates the connections between ET innovation and sustainable development and discusses the implementation of ET innovation at a firm level. The firms selected for this study focused on the whole spectrum of ET innovation when implementing their environmental technologies. These firms also targeted international markets with their eco-products and green technologies. However, we established that they need to become more market-oriented during the development of their products and technologies so that they address market needs. The involvement of firms in ET innovation requires significant investment in R&D and the proper management of resources to be successful.